SEBACEOUS CYSTS MINOR SURGERY - Agung Laksemi, I Gusti Ayu; Maliawan, Sri; Kawiyana, Ketut Siki (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Minor surgery is small surgery or localized example cut ulcers and boils, cyst excision, and suturing. Somethings that need to be considered in the preparation of the surgery is minor tools, operating rooms and operating tables, lighting, maintenance of tools and equipment, sterilization and desinfection equipment, preparation of patients and anesthesia. In general cysts is walled chamber that consist of fluid, cells and the remaining cells. Cysts are formed not due to inflammation although then be inflamed. Lining of the cysts wall is composed of fibrous tissue and usually coated epithelial cells or endothelial. Cysts formed by dilated glands and closed channels, glands, blood vessels, lymph channels or layers of the epidermis. Contents of the cysts wall consists of the results is serum, lymph, sweat sebum, epithelial cells, the stratum corneum, and hair. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Cysts Minor Surgery